Effect of Moringa Leaf Ethanol Extract on Reduced Levels of Mda, TNF-α and Description of Inflammatory Cells in Rat Sinus Mucosa Model of Acute Rhinosinusitis (Bangladesh Journal of Medical Science, 2022)
Background: Symptoms and signs of acute viral and bacterial rhinosinusitis that are not specific cause difficulties in diagnostic enforcement, causing difficulties in administering therapy, so often doctors provide antibiotic therapy on acute viral rhinosinusitis. Irrelevant antibiotics will cause frequent antibiotic resistance. Adjuvant therapy is required to prevent infections that continue to become chronic, shorten the duration of infection, and avoid unwanted complications. Moringa leaves (M. oleifera)contains antioxidant components that can help rebalance redox metabolism and reduce excess free radicals so as to prevent oxidative stress.Method: posttest only control group research design. Male strain Sprague Dawley white rat was maintained and treated at the Nutrition Laboratory of the Center for Food and Nutrition Studies of Gadjah Mada University (UGM). Mice were divided into 4 groups. Group 1: standard feed., group 2: standard feed and staphylococcus-induced aureus, group 3: standard feed, Staphylococcus aureus-induced given amoxicillin dose of 27 mg/day, group 4: standard feed, Staphylococcus aureus-induced was given amoxicillin dose of 27 mg/day and given (EEDK) 200 mg/KgBW/day. Data analysis Of Normality test using Shapiro-Wilk Test and homogeneity using Levene’s Test obtained results p>0.05. Then conducted One Way AnovaTest obtained p